Infections with a Malaysian dog strain of Ancylostoma ceylanicum in outbred, inbred and immunocompromised mice - Carroll, S. M.; Grove, D. I.; S., H. J.; Mitchella, G. F.; Whitten, L. K. (1983)
The course of infection with a Malaysian dog strain of Ancylostoma ceylanicum was investigated in 15 inbred strains of mice, in outbred and inbred mice immunosuppressed with prednisolone, and in immuno-deficient hypothymic mice. Oral, percutaneous and subcutaneous routes of infection, in both sexes of mice, were assessed. In only one instance was a single small adult male worm found. Following oral infection, larvae migrated from the stomach to the large bowel and then a proportion of worms penetrated the perianal skin. This was followed by the appearance of larvae in the lungs. Living 3rd-stage larvae were seen in the anterior small intestine, perianal skin and lungs for the 6 weeks of the study, with peak recoveries being at 12 h, 8 days and 3 weeks, respectively. It is clear that systemic migration of larvae occurs after oral infection, and it is possible that recirculation may occur. Only a small percentage of larvae penetrated the abdominal skin after being administered percutaneously. In subcutaneous infections, a small proportion of larvae moved rapidly from the site of injection and were recovered from the lungs 2 h after infection. Most larvae, however, migrated from the injection site over the ensuing few days. Living 3rd-stage larvae were seen in the lungs and in the small intestine for the 4 weeks of observation. The strain of A. ceylanicum employed does not complete its development in mice. Nevertheless, this model offers significant potential for studying the immune responses, as well as investigating the means by which these parasites evade host defences. © 1983, Cambridge University Press. All rights reserved.